The impact of social determinants on schoolchildren's oral health in Brazil - Janice Simpson de PAULA; Glaucia Maria Bovi AMBROSANO; Fábio Luiz MIALHE (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to evaluate the impact of socioeconomic status, home environment, and self-perception of health conditions on schoolchildren's dental caries experience. A total of 515 twelve-year-old schoolchildren from Juiz de Fora, State of Minas Gerais, Brazil, were selected into a random multistage sample. The schoolchildren were examined for the presence of caries lesions using the decayed/missing/filled teeth (DMFT) index and categorized as caries-free (DMFT = 0) or with caries experience (DMFT > 0). The participants and their parents were asked to answer a questionnaire about socioeconomic status, home environment, and self-perception of their health conditions. The hierarchical multiple regression model was used to assess the associations, since a binary response variable was assumed. The bivariate analysis revealed that variables at four levels, such as type of school, monthly family income, parents' education, home ownership, number of people living in the household, household overcrowding, parents' perception of their children's oral health, and schoolchildren's self-perception of their oral health (p < 0.05), were significantly associated with children's worse dental caries conditions. The regression model results showed that type of school and monthly family income had a strong negative effect on schoolchildren's dental caries experience (p < 0.05) in the final statistical model, where all levels were included. It was observed that socioeconomic factors were considered a strong risk indicator of schoolchildren's caries experience among the investigated social determinants of oral health.